Analysis Study Of The 2009 MUI Fatwa About The Law Of Early Marriage - Dony Frenki; Eficandra, Eficandra; Yengkie Hirawan (International Journal of Education, Vocational and Social Science, 2022)
Marriage is an act recommended by Allah and by the Prophet, this can be seen in the Al-Qur'an and the Hadith of the Prophet where the content is in the form of a recommendation to marry. In 2009, the MUI issued a ijtima' decision on early marriage. According to the MUI, early marriage is legal as long as the conditions and pillars of marriage have been fulfilled, but it is illegal if it causes harm. In terms of maṣlāḥah, early marriage is not against Islamic law, because marriage aims to create problems. However, the impacts arising from early marriage tend not to bring problems to the marriage partner. This is the focus of this research. The research question is what is the background to the emergence of the 2009 MUI Fatwa on the Law on Early Marriage, what is the intention of getting married at an early age unlawful if there is concern that harm will arise in the MUI fatwa. According to existing regulations, the age for student acceptance is for elementary school students in the age range of seven years to a maximum of 12 years and a minimum of six years on July 1 of the current year. Then junior high school students with a maximum age of 15 years and high school 21 years. This means that according to applicable regulations, high school students are allowed to marry because they are between 21 and 23 years old. An in-depth study is needed on this matter.